Sensitivity of the Footeval Test to Different Training Modes. Issue 5 (May 2020) - Manouvrier, Christophe; Cassirame, Johan; Ahmaidi, Said
Abstract : Abstract: Manouvrier, C, Cassirame, J, and Ahmaidi, S. Sensitivity of the footeval test to different training modes. J Strength Cond Res 34(5): 1440–1447, 2020—The aim of this study is to assess the impact of preseason training and more specifically about different training modality to Footeval test. This study also compares those sensibility with classic test, Vameval. A total of 36 young elite players' performance were split in 3 groups to perform 2 times a week a specific complements training: generic (GENERIC), small-sided game (SSG), and technical (TECH). After 4 weeks with training intervention, all players improved their performance to Footeval and Vameval tests. Regarding improvement, we noted that each training complement obtained different magnitude of modification. For all groups, Footeval increase was more important than Vameval. Small-sided game obtained highest improvement to Footeval (15 ± 1.8%) but lowest to Vameval (5 ± 0.9%). Oppositely, GENERIC and TECH groups obtained highest improvement to Vameval test (8 ± 1.4 and 8 ± 2.0%) but lower modification to Footeval (11 ± 2.2 and 16 ± 2.3%), respectively. Even if we removed the effect of maximum aerobic speed increase, SSG obtains better improvement than other training modality to Footeval.